Tracking Kinematic Gait Parameters During the Recovery of Motor Function After Total Knee Arthroplasty. (2016) - Mihalcica, Mircea; Modrea, Arina; Munteanu, Violeta; Burca, Ioan
Abstract: One of the important issues concerning physical medicine and rehabilitation, especially in underdeveloped countries, is tracking the progress of recovery for a patient by using more than clinical parameters. Unfortunately, in low income countries (but not only), for financial reasons, many patients do not even follow a recommended recovery and rehabilitation exercise program, and, from those who do, only a few benefit from specifically customized ones. In this paper we present a series of gait parameters which are important for the rehabilitation for patients in motor functions recovery. The data is collected and the gait parameters are obtained with the help of an inexpensive and portable motion analysis system, suitable for implementation in low income countries. By analyzing these parameters, we prove that, considering the gait perspective, three patients who have been treated using the same surgical procedure recover their motor abilities differently from each other. This proves the importance of a customized recovery program, which does not rely only on the clinical approach.